CONSOLIDATION OF CLAYEY SUB-SOILS WITH INTERMEDIATE PERMEABLE LAYERS IMPROVED BY VERTICAL DRAINS WITH SMEAR EFFECT - G. Imai; U. P. Nawagamuwa (International Association of Lowland Technology, 2005)
Design of vertical drains is usually based on Barron's theory considering the clay layer is always homogeneous. However it has often been recognized in several situations that many natural deposits have considerable in-homogeneities, such as laminations of coarser material within the clay layer. Field data from such clay layers improved by vertical drains have sometimes shown that the commonly used conventional equations should be modified. In this paper, considering horizontal and vertical inflow and outflow into and out from a small element, governing equation of consolidation has been formulated with the effects of varying permeability and compressibility with time. Two kinds of new parameters are defined as K=(ks/kc)(Hs/Hc) and α98=t98(2D)/t98(radial) considering different coefficients of permeability and sand/clay thickness. With these definitions, the importance of thin intermediate permeable layers, which were previously overlooked in designs, are discussed in this paper. The variation of ch/cv back calculated from the insitu tests are assessed with the above theoretical concepts considering both effects of smear and intermediate permeable layers. Practical approaches for measuring insitu permeability and thickness of intermediate permeable layers for better prediction are also included.